2019
DOI: 10.1097/ncc.0000000000000685
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Self-efficacy for Symptom Management in the Acute Phase of Hematopoietic Stem Cell Transplantation

Abstract: Background Hematopoietic stem cell transplantation (HSCT) is an intensive treatment that offers the potential for longer life or cure for some types of cancer. Hematopoietic stem cell transplant is associated with decreased quality of life and functional status and distressing symptoms. Self-efficacy for symptom management (SESM) is a person's belief in his/her ability to implement behaviors to manage these symptoms. Presence of SESM can affect symptom distress, healthcare utilization, and posttran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Still, the additional value of the nurse-led patient navigation intervention, even in this group, is visible in this study, especially for the more practical and emotional domains of daily life. Cancer nurses should therefore be recognized as key members of the survivorship care team 30–32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the additional value of the nurse-led patient navigation intervention, even in this group, is visible in this study, especially for the more practical and emotional domains of daily life. Cancer nurses should therefore be recognized as key members of the survivorship care team 30–32 …”
Section: Discussionmentioning
confidence: 99%
“…Cancer nurses should therefore be recognized as key members of the survivorship care team. [30][31][32] Despite the significant improvement of QoL over time in the IG, no differences in QoL were observed between the IG and the CG 1 year after transplantation. This improvement of QoL in the IG might be explained by a gradual improvement of the medical situation and the physical and psychosocial recovery after HSCT.…”
mentioning
confidence: 92%
“…This practice of nonjudgmental present-moment awareness has been demonstrated to reduce stress, 33 increase selfefficacy, 34 and improve emotion regulation 35 all of which have been associated with reductions in anxiety and depression among cancer patients/survivors. [36][37][38] Khoury and colleagues 39 suggest that mindfulness-based therapies may be most effective in those with more severe mental illness (ie, depression). In a meta-analytic review, they found across multiple studies (n = 6) that those reporting a more severe level of baseline depression improved to a greater extent from pretreatment to posttreatment as compared with those reporting more mild or moderate depression at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…HSCT is among the treatment approaches that prolong the life of patients with lymphoma, improve their quality of life, achieve remission success and reduce the incidence of relapse [11,14]. Although SCT contributes positively to the recovery process of patients with lymphoma, it causes patients to face many social, economic, and psychological problems [15,16]. Patients experience many symptoms depending on the disease and treatment process, and in this case, their life processes are affected and the satisfaction from life is prevented [3,9].…”
Section: Introductionmentioning
confidence: 99%